Self-Portrait. - Prince, Morton. (Tufts University. Tisch Library., 2017)
Abstract: Dr. Morton Henry Prince 1854-1929; Boston physician and specialist in nervous diseases and abnormal psychology; appointed Professor Diseases of the Nervous System at Tufts College Medical School in 1902; established the Journal of Abnormal Psychology in 1906; leading investigator of the pathology of mental disorders and directed the Harvard Psychological Clinic; awarded an honorary degree from Tufts College in 1910. See similar portrait AI41500. Date created: ca 1900. Medium: Oil on canvas. Measurements in inches: 18.000 H. x 14.000 W.